Pengembangan YouTube Sebagai Bahan Belajar Mandiri pada Subjek Pertidaksamaan Linear Satu Variabel Tingkat SMP - Cici Naftalie Alleztin Pambudi; I Nyoman Arcana; Zainnur Wijayanto (UNION : Jurnal Ilmiah Pendidikan Matematika, 2021)
This study aims to develop YouTube in the form of video as independent study material on one variabel linear inequality and determine its feasibility. The method used in this research is a research and development method with the ADDIE development model through 5 stages, namely Analysis, Design, Development, Implementation, and Evaluation. The research was conducted at SMP Negeri 2 Pandak with 26 students as the subject of class VII E. Data collection techniques used student response questionnaires and learning outcomes tests. The result of this research is a mathematics learning video product that is presented through YouTube under the account name "Cinta Matematika Kuy". Assessments from media experts and material experts show that the development of YouTube as an independent learning material falls into the very valid category with an average value of 4.57. The results of the correlation between the student response questionnaire and the learning outcome test also showed a very strong relationship. Thus, the YouTube video developed was feasible to use.